Confirmation of Ostracotheres H. Milne Edwards, 1853 from Southeast Asia in a new species from Singapore and Indonesia (Crustacea: Decapoda: Brachyura) - Ahyong, Shane T.; Mendoza, Jose Christopher E. (Zootaxa, 2024)
A new species of the pinnotherid crab genus Ostracotheres H. Milne Edwards, 1853 described from Singapore and Indonesia is the third species in the genus, previously represented by O. cynthiae Nobili, 1906 and O. tridacnae (Rüppell, 1830) (type species), both known only from the Red Sea and western Gulf of Aden. Therefore, the new species represents the first confirmed record of the Ostracotheres outside of the western Indian Ocean and the twelfth species and ninth genus of pinnotherid to be recorded from Singapore. The new species is closest to O. cynthiae, differing in details of the epistome, ornamentation of the walking leg dactyli and proportional lengths of the walking legs. A key to the species of Ostracotheres is provided.